I’RAB DAN TAFSIR QS. ALI IMRAN AYAT 190 DAN AL-A’RAF AYAT 180: STUDI KEBAHASAAN DAN MAKNA DALAM PENGENALAN ALLAH - Afriazil Arief Saimin; Ahmad Husni (Adisam Publisher, 2025)
This research examines how to know Allah from the perspective of the Qur'an, Surah Ali Imran verse 190 and Surah Al-A'raf verse 180. Where, humans must of course know who is the creator, the provider of their sustenance, the one who organizes and takes care of it. Apart from that, this research also analyzes language through studying the i'rab of the Qur'an and tafsir to find out how to know Allah and his wisdom through these verses. This research uses a qualitative approach with a literature study method. Data and information are collected and then analyzed according to the study and research objectives. By studying the i'rab and interpretation of QS. Ali Imran verse 190 and QS. Al-A'raf verse 180 can get to know Allah SWT more closely. In this case, know His existence, greatness and names well.